Eye Movement Desensitization and Reprocessing vs. Treatment-as-Usual for Non-Specific Chronic Back Pain Patients with Psychological Trauma: A Randomized Controlled Pilot Study - Gerhardt, Andreas; Leisner, Sabine; Hartmann, Mechthild; Janke, Susanne; Seidler, Günter H.; Eich, Wolfgang; Tesarz, Jonas (Frontiers in Psychiatry, 2016)
Objective Eye movement desensitization and reprocessing (EMDR)—an evidence-based approach to eliminate emotional distress from traumatic experiences—was recently suggested for the treatment of chronic pain. The aim of this study was to estimate preliminary efficacy of a pain-focused EMDR intervention for the treatment of non-specific chronic back pain (CBP). Design Randomized controlled pilot study. Methods 40 non-specific CBP (nsCBP) patients reporting previous experiences of psychological trauma were consecutively recruited from outpatient tertiary care pain centers. After baseline assessment, patients were randomized to intervention or control group (1:1). The intervention group received 10 sessions standardized pain-focused EMDR in addition to treatment-as-usual (TAU). The control group received TAU alone. The primary outcome was preliminary efficacy, measured by pain intensity, disability, and treatment satisfaction from the patients’ perspective. Clinical relevance of changes was determined according to the established recommendations. Assessments were conducted at the baseline, posttreatment, and at a 6-month follow-up. Intention-to-treat analysis with last observation carried forward method was used. Registered with http://ClinicalTrials.gov (NCT01850875). Results Estimated effect sizes (between-group, pooled SD) for pain intensity and disability were d = 0.79 (CI95%: 0.13, 1.42) and d = 0.39 (CI95%: −0.24, 1.01) posttreatment, and d = 0.50 (CI95%: 0.14, 1.12) and d = 0.14 (CI95%: −0.48, 0.76) at 6-month follow-up. Evaluation on individual patient basis showed that about 50% of the patients in the intervention group improved clinically relevant and also rated their situation as clinically satisfactory improved, compared to 0 patients in the control group. Conclusion There is preliminary evidence that pain-focused EMDR might be useful for nsCBP patients with previous experiences of psychological trauma, with benefits for pain intensity maintained over 6 months.